Recent advances in basic and translational stroke research. (February 2011) - Boltze, Johannes; Kranz, Alexander; Wagner, Daniel-Christoph; Reymann, Klaus; Reiser, Georg; Hess, David C
Since 1998, the biannual International Symposium on Neuroprotection and Neurorepair, also known as the Magdeburg Meeting series, has provided a platform for the discussion of recent advances in basic and translational stroke research. The 2010 meeting reviewed highly relevant topics, including astrogliosis and microgliosis, neuroimmunological processes, cell-based therapies, novel imaging approaches, mechanisms of poststroke regeneration and metabolic phenomena in neuroprotection. It further focused on common pitfalls and opportunities in the translational process, from preclinical research to clinical application.